Coping with the Challenges of Higher Education in the Twenty-first Century - Kajubi, William Senteza (Effective Teaching in Higher Education. Entebbe: Nkumba University, 2001)
The importance of education today, more than ever before, cannot be overemphasised. Education is the key to addressing some, if no all the major problems confronting the world during out time. Challenges such as respect for human rights, democracy and the promotion of peace, preservation of the ecosystem, combating corruption, ethnicity, genocide and all forms of violence against society are intimately linked to the problem of education.Increased investment in education, even basic education can stimulate development in many ways. For example, educated farmers are more likely generally to achieve higher productivity than those who have not been to school, and research has also established that mothers' education enhances the probability of child survival and development, and in industry an educated and healthy labour force, capable of learning new skills is a great economic asset.When it comes to civic affairs, there is no doubt that democracy works better among literate voters who are able to read the newspapers, listen to the mass media critically and are able to analyse and grasp the issues at stake than among illiterate voters who may base their judgements on the opinions of others. Surely, education is the gateway to empowering the people with the basic cognitive skills in order to render them self-reliant participating citizens.On the other hand cost-benefit studies conducted in a number of African countries during the late 1980s suggested that the social returns on investment in education were greater at the primary than at the higher levels; being 26 per cent for Primary, 17 percent for secondary, and 13 percent for higher education. [The World Bank 1989 p.77] In other words the social benefits increased in an inverse proportion to the level of education. Because of this, basic education has been assigned a higher priority than higher education in the Less Developed countries. Since the 1980's international funding agencies the World Bank and IMF, and national governments and private investors in Africa have also generally assigned a lower priority to higher education vis-a-vis primary schooling. Higher education, apart from yielding lower returns, was regarded as being unduly expensive, elitist and exclusive, and produced unemployed and unemployable graduates. The tide has now turned. There is a New World order in which information, scientific and technological knowledge and higher order skills have a higher economic premium than physical capital. The growing economic importance and proliferation of knowledge, the cut-throat competition in all sectors of the world economy and the stream of secondary school leavers seeking admission to universities have combined to make higher education more important today than it has ever been before. The old adage that knowledge is power has never been truer than it is today. There is an enhanced demand for high-level skills, particularly in science and technology, and those countries which are able to produce or acquire them have inestimable advantages over those which are not in position to do so. The industrial countries are engaged in a mad rat race based on computers and information technology to exert greater control over their competitors and the developing world. The North-South gap between the industrially developed nations and the less developed world is, therefore, widening fast. It is now realised even in the less developed countries hat higher education is a necessary condition for participation and effective competition in the global markets, so as to narrow if not bridge that gap. This situation poses dilemmas for the LDCs and new challenges for higher education in Africa. The purpose of this paper is to address the implications of the New World order and some of the challenges they pose for higher education in Africa with specific reference to Uganda. Can higher education help to improve the quality of life in our countries, and to narrow the North-South Gap? What are the major obstacles in its way, and how can they be overcome or at least ameliorated? An attempt is made to suggest some coping strategies for universities.